Creative methodology of da’wah through different phases of human’s life - U Tun Aung, Maulana Akbar Shah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
After compliance to the five pillars of Islam, Daw’ah Islamia is indispensable act for those Muslims who seriously think his life and his mission is assigned for propagation of Islam. Act of Daw’ah is a mission only undertaken by those whom are selected to do so as Allah SWT said: “You are the best of peoples, taken out for mankind, you enjoin what is right, forbid what is wrong…,”( Al-Qur’an, Aal `Imran, 3:110). Here “you are taken out for mankind” is a very clear phrase for special selection of a group. Many Da’ie propagate their activities through the regular procedure. In this contemporary time, it would be more successful, if some creative Daw’ah methodology is used in some uncommon zone where special talent is required. For instances, people like [1] Pregnant mother [2] Mothers of New Born Baby, [3] Parents of Toddlers, [4] Parents of children [5] youths, Teenagers and Adolescence [6] Married Couples, [7] Elders or aged people [8] Non-Muslims happened to be the targets to promote Islam, then Da’ie must have a special talent and knowledge to do so. In this regard, Da’ie must equip with some exceptional knowledge of these people to propagate Islam. This paper attempts to highlight distinctive nature of the said category and inform Da’ies how he should approach them in case he encounters them for the purpose of promotion of Islam.